ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH GO PUBLIC PADA BURSA EFEK INDONESIA - Jefri Pranata; Debora Tambunan; Emma Novirsari (Jurnal Mahkota Bisnis (Makbis), 2024)
To determine the financial performance of a company, an assessment needs to be carried out. In this research, an assessment was carried out using liquidity, activity, profitability and solvency ratios. By calculating using these ratios, the public can find out whether a company's finances are healthy or not, so that the public can consider whether they want to buy shares in a company. This research aims to examine the influence of company finances before and after Go-Public on the Indonesian Stock Exchange (BEI). The population in this study was 20 companies. The sample for this study used purposive sampling and a sample of 5 companies was obtained. The sample collection technique uses a purposive sampling method, namely taking research samples by paying attention to certain criteria based on the research objectives. Data analysis used multiple linear regression with the help of SPSS software. The results of research on the liquidity ratio show a significance rate of 1.146, where this value is greater than the probability limit of 0.05. This shows that there is a significant decline in the liquidity ratio for the 2 years before and 2 years after going public. This happens because the company receives additional funds from the public, but these funds are not used to fulfill the company's short-term financial obligations so they cannot reduce the debts the company bears